Efektivitas Teknik Relaksasi Benson terhadap Penurunan Nyeri Akut pada Pasien Pasca Appendiktomi: Studi Kasus: The Effectiveness of the Benson Relaxation Technique on Acute Pain Reduction in Post-Appendectomy Patients: A Case Study - Sihombing , Riris Yuniwati; Suranta, Tomi; Bangun , Argi Virgona; Hutasoit, Mey Lys C (Chakra Brahmanda Lentera Institute, 2026)
Acute pain is a common issue in post-appendectomy patients, potentially delaying recovery, increasing anxiety, and hindering early mobilization. Benson relaxation technique, as a non-pharmacological intervention, is believed to reduce pain, but its effectiveness in appendectomy patients requires further empirical evidence. This study aims to analyze the effectiveness of the Benson relaxation technique in reducing acute pain intensity in post-appendectomy patients. The research design used is a case study with a complete nursing care approach (assessment, diagnosis, intervention, implementation, evaluation). One post-appendectomy patient in Ward 10 of Mandaya Royal Puri Hospital received the Benson relaxation technique intervention for three consecutive days, in addition to standard pharmacological therapy. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after the intervention. Results showed a reduction in pain scale from 7 (severe) on the first day to 5 (moderate) on the second day, and finally to 0 (no pain) on the third day. The Benson relaxation technique proved effective as a supportive intervention in reducing acute pain, improving comfort, and reducing anxiety and mobility limitations in post-appendectomy patients. This intervention is recommended for routine implementation in post-abdominal surgery nursing care.